Protective effect of intraluminal fecal diverting device against colonic wall erosion induced by wrapping bands: A post-hoc pathological analysis - Kang, Sung Il; Kim, Sohyun; Gu, Mi Jin; Hwang Kim, Jae (Turkish Journal of Surgery, 2022)
Objective: Materials wrapping the bowel elicits tissue erosion gradually. We experienced several bowel wall erosions with no serious clinical consequences in our two previous animal experiments aimed at the safety and efficacy of the COLO-BT developed for intra-luminal fecal diversion. We tried to find out why the erosion is safe by investigating histologic changes of the tissue. Material and Methods: Tissue slides at the COLO-BT fixing area from the subjects which had COLO-BT over three weeks acquired from our two previous animal experiments were reviewed. For the classification of the histologic change, microscopic findings were classified for six stages (from minimal change of stage 1 to severe change of stage 6). Results: A total of 26 slides of 45 subjects were reviewed in this study. Five subjects (19.2%) had stage 6 histological change; three of stage 1 (11.5%), four of stage 2 (15.4%), six of stage 3 (23.1%), three of stage 4 (11.5%), and five of stage 5 (19.2%). All subjects which had a stage 6 histologic change survived. The phenomenon from which the back of the band is passed through is replaced by a relatively stable tissue layer due to fibrosis of the necrotic cells in the stage 6 histologic change. Conclusion: We found that thanks to the sealing effect of the newly replaced layer, no leakage of the intestinal content occurs even if perforation by erosion develops according to this histologic tissue evaluation.